Agricultural and landscape factors related to increasing wild boar agricultural damage in a highly anthropogenic landscape. Issue 1 (26th December 2019) - Rutten, Anneleen; Casaer, Jim; Strubbe, Diederik; Leirs, Herwig
Abstract : Human–wildlife impacts (HWI) occur due to interactions between wildlife and human activities in our increasingly anthropogenic world and typically result in economic losses or increased health‐ and safety risks. HWI can be especially prevalent where urbanization encroaches upon natural areas, or in fragmented human‐dominated landscapes. An example of such situation is the re‐occurrence of wild boar in Flanders (northern Belgium). Flanders is one of the most densely populated areas of Europe and is characterized by a severely fragmented landscape. The recent return of wild boar to Flanders challenges managers to find solutions for a sustainable co‐existence between humans and wild boar. As crop damage is increasing and targeting preventive measures efficient requires identifying high risk areas, we assessed the influence of the landscape around a field, as well as field‐specific characteristics on the likelihood of wild boar crop damage. Because most of the reported damage in Flanders occurs in grasslands (cultivated to produce hay) and maize fields, we focused on these. We used boosted regression trees and the brglm‐technique to construct distribution models explaining spatial patterns of crop damage. We found that for maize fields, landscape‐level variables such as the proportion of maize, grassland, forest and urbanized areas in the surroundings of the field are key factors determining the probability of damage. In contrast, field‐specific variables only played a minor role. For grasslands, both field‐specific and landscape characteristics affected damage probability: a higher probability of damage was associated with decreasing distance to nearest forest, increasing distance to the nearest road, the use of inorganic fertilization and increasing age of the grassland. Our results suggest that the risk of crop damage by wild boar can potentially be mitigated by changes in agricultural practices that alter grassland characteristics, and by targeting preventive measures towards high risk maize in well‐defined locations.